Videoland : Movie Culture at the American Video Store - Herbert, Daniel, 1974- (Book collections on Project MUSE., 2014)
Videoland offers a comprehensive view of the ""tangible phase"" of consumer video, when Americans largely accessed movies as material commodities at video rental stores. Video stores served as a vital locus of movie culture from the early 1980s until the early 2000s, changing the way Americans socialized around movies and collectively made movies meaningful. When films became tangible as magnetic tapes and plastic discs, movie culture flowed out from the theater and the living room, entered the public retail space, and became conflated with shopping and salesmanship. In this process, video sto.